DETERMINATION OF THE CEMENTED LAYER THICKNESS OF CHROME-NICKEL STEELS - A. L. Valko; E. I. Mosunov; S. P. Rudenko; N. P. Timoshenko (Литьë и металлургия)
It is shown that the thickness of cemented layer defined after cementation by samples from steel 12Хн3А, is overstated by 0,20–0,35 mm because of higher content of nickel.